Photochromic functional ceramic material and application thereof
By coating nano-silica on the surface of nano-alumina and modifying it with an amino-containing silane coupling agent, combined with a functionalized binder, the problem of agglomeration of nano-sodium niobate-based materials during sintering was solved, and the mechanical properties of photochromic functional ceramics were improved.
Patent Information
- Application Number
- CN202510966485.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-07-14
AI Technical Summary
During the sintering process of nano-sodium niobate-based materials, nano-alumina is prone to agglomeration, resulting in a decrease in density and affecting mechanical strength.
The reinforcing component is prepared by coating nano-silicon dioxide on the surface of nano-alumina and modifying it with an amino-containing silane coupling agent, and a functionalized binder is added to improve the mechanical properties.
The mechanical properties of the photochromic functional ceramic material are improved, and the toughness and bending strength of the ceramic material are enhanced.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional ceramic preparation, and more particularly to a photochromic functional ceramic material and its application. Background Art
[0002] As an important component of functional ceramics, photochromic materials are widely used in functional ceramic parts and electronic components due to their unique photoinduction and superior photoresponse reversibility.
[0003] Sodium niobate-based compound materials, as an important component of photochromic materials, have excellent plasticity and high photoelectric conversion efficiency. However, although sodium niobate-based materials have high hardness, their own toughness and flexural strength are average. The existing use of nano-aluminum oxide to toughen nano-sodium niobate-based materials can significantly improve the toughness and mechanical strength of nano-sodium niobate-based materials. However, during the sintering process of sodium niobate-based materials, nano-aluminum oxide is prone to agglomeration, resulting in a decrease in the density of the nano-sodium niobate-based materials, which affects the mechanical strength of the nano-sodium niobate-based materials.
[0004] Based on the above statements, the present invention provides a photochromic functional ceramic material with excellent mechanical properties and its application. Summary of the Invention
[0005] In order to solve the problems mentioned in the above background technology, the present invention provides a photochromic functional ceramic material and its application.
[0006] A photochromic functional ceramic material, comprising a photochromic material, a reinforcing component, a functionalized binder and a solvent;
[0007] The present invention also provides a method for preparing the photochromic functional ceramic material described in the above technical solution, comprising the following steps:
[0008] Step S1, primary grinding: niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide, and anhydrous ethanol are mixed, wet ball milled, dried, and sieved to obtain a primary grinding material, wherein the mass ratio of niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide, and anhydrous ethanol is 36.3:1-5:7.3-13.1:0.17-0.21:500-600;
[0009] Step S2, preparing a photochromic material: placing the primary ground material in a high-temperature sintering furnace for pre-sintering, and cooling to room temperature to obtain a photochromic material;
[0010] Step S3, preparing a green body: adding a photochromic material to a solvent, performing secondary grinding, then adding a reinforcing component, a functionalized binder, and a catalyst, stirring evenly, placing the green body in a mold, and performing dry pressing and cold isostatic pressing to obtain a green body, wherein the mass ratio of the photochromic material, the solvent, the reinforcing component, the functionalized binder, and the catalyst is 90-100:42-46:8-12:10-16:0.2-0.6;
[0011] Step S4, preparing a photochromic functional ceramic material: placing the green body into an alumina crucible, placing it in a high-temperature box furnace, performing a binder removal process, then performing high-temperature sintering, and cooling to room temperature to obtain a photochromic functional ceramic material.
[0012] Application of the photochromic functional ceramic material prepared by the method in functional ceramic parts.
[0013] Preferably, in step S1, the wet ball milling treatment is specifically as follows: the ball milling speed is 480-540 rpm, and the ball milling time is 22-26 h.
[0014] Preferably, in step S2, the pre-sintering process is to heat the material to 920-980°C at a heating rate of 1-3°C / min and keep the temperature for 1.8-2.2h.
[0015] Preferably, in step S3, the solvent is an ethanol aqueous solution with a mass fraction of 8-12%.
[0016] Preferably, in step S3, the catalyst is p-toluenesulfonic acid or pyridine.
[0017] Preferably, in step S3, during the dry pressing process, the pressure is 6-8 MPa, the holding time is 1-2 min, the cold isostatic pressing pressure is 260-320 MPa, the cold isostatic pressing temperature is 64-72° C., and the cold isostatic pressing time is 2-4 min.
[0018] Preferably, in step S4, the debinding treatment is to heat the temperature to 540-560°C at a heating rate of 1-3°C and keep it warm for 4.5-5.5h, and the sintering treatment is to heat the temperature to 1220-1320°C at a heating rate of 3-5°C / min and keep it warm for 3.6-4h.
[0019] Preferably, the reinforcing component is prepared by the following steps:
[0020] Step A1, adding a saturated aluminum sulfate solution dropwise to a sodium metaaluminate aqueous solution while stirring, controlling the dripping to be completed within 15 minutes, continuing to stir for 18-22 minutes to obtain a gel, vacuum filtering the gel to obtain a filter cake, adding the filter cake to an ethanol aqueous solution, stirring evenly, adjusting the pH value to 8.8-9.2, then adding ethyl orthosilicate, heating to 50-66°C, continuing to stir and react for 1.2-1.6 hours, centrifuging, washing the precipitate, and drying to obtain core-shell particles, wherein the mass ratio of the saturated aluminum sulfate solution, the sodium metaaluminate aqueous solution, the ethyl orthosilicate, and the ethanol aqueous solution is 10-14:18-30:50-60:450-550. During the above reaction process, aluminum hydroxide gel is obtained by precipitation method, and then the aluminum hydroxide gel is coated with silica obtained by hydrolysis of the ethyl orthosilicate to obtain core-shell particles;
[0021] Step A2, adding the core-shell particles to deionized water, heating to 35-45°C, ultrasonically treating for 8-12 minutes, and adding a mixture of a silane coupling agent and anhydrous ethanol dropwise while stirring. The dripping is controlled to be completed within 15 minutes. After the dripping is completed, the temperature is raised to 45-55°C, stirring and reacting for 2.2-2.4 hours, centrifuging, washing the precipitate, and drying to obtain a reinforcing component, wherein the mass ratio of the core-shell particles, deionized water, and the mixture a is 3-5:55-65:28-32, and the mass ratio of the silane coupling agent and anhydrous ethanol in the mixture a is 0.4-0.8:30. During the above reaction process, the core-shell particles are treated with the silane coupling agent to obtain the reinforcing component.
[0022] Preferably, in step A1, the concentration of the sodium metaaluminate aqueous solution is 3-4 M, and the mass fraction of the ethanol aqueous solution is 8-12%.
[0023] Preferably, in step A2, the silane coupling agent is γ-aminopropyltriethoxysilane or γ-aminopropylmethyldiethoxysilane.
[0024] Preferably, the functionalized adhesive is prepared by the following steps:
[0025] Dopamine and polyacrylic acid are added to a Tris-HCl buffer solution with a pH of 8-9, stirred evenly, and then silica sol is added. The temperature is raised to 34-40°C, and stirring is continued for 12-16 minutes to obtain a functionalized adhesive, wherein the mass ratio of dopamine, polyacrylic acid, Tris-HCl buffer solution and silica sol is 2-3:10-14:50-60:0.8-1.2.
[0026] Preferably, the mass fraction of silica sol is 30-40%.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] In order to improve the mechanical properties of photochromic functional ceramic materials, the technical solution of the present invention starts from two aspects. First, nano-silicon dioxide is coated on the surface of nano-alumina, and then it is modified by a silane coupling agent containing amino groups to prepare a reinforcing component. The coating not only reduces the surface activity of nano-alumina, reduces the agglomeration of nano-alumina particles due to chemical bonding or hydrogen bonding, and improves the mechanical properties of the ceramic material, but also during the high-temperature sintering process, alumina can generate mullite phase with silicon dioxide, further improving the mechanical properties of the ceramic material. At the same time, the amino group can also produce chemical cross-linking with the carboxyl group in the functionalized binder, further improving the mechanical properties of the functional ceramic material. The mechanical properties of the porcelain material are improved; secondly, a functionalized binder is added. The functionalized binder is compounded by dopamine, polyacrylic acid and silica sol. The phenolic hydroxyl structure contained in dopamine has good adhesion, and dopamine can self-polymerize in Tris-HCl buffer. The obtained polydopamine molecule contains rich active amino groups, which can not only form hydrogen bonds with the hydroxyl groups in the silica sol and the amino groups in the reinforcing component, but also form chemical bonds with polyacrylic acid. The presence of silica sol improves the compatibility between the functionalized binder and the reinforcing component. Introducing it into the functional ceramic material can synergize with the reinforcing component to jointly improve the mechanical properties of the photochromic functional ceramics. DETAILED DESCRIPTION
[0029] In order to make the embodiments of the present invention easier to understand, the present invention will be described in detail below with reference to specific examples. These examples are only for illustration and do not limit the scope of application of the present invention.
[0030] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0031] The silica sol is industrial grade silica sol produced by Guangdong Kening Technology Co., Ltd. with CAS No. 13318397072. The polyacrylic acid is a high-quality polyacrylic acid commercially available from Jinan Xinguan Chemical Products Co., Ltd. with CAS No. 659-98-01. The polyvinyl alcohol is produced by Shandong Jinyufeng New Materials Co., Ltd. with CAS No. 9002-89-5.
[0032] The present invention is further described in detail below with reference to Examples and Comparative Examples.
[0033] Preparation Examples 1-3 and Comparative Preparation Examples 1-3 provide a reinforcing component.
[0034] Preparation Example 1
[0035] This preparation example provides a reinforcing component, which is prepared by the following steps:
[0036] Step A1, at a speed of 540 rpm, adding a saturated aluminum sulfate solution dropwise to a sodium aluminate aqueous solution while stirring, controlling the dripping to be completed within 15 minutes, maintaining the speed unchanged, and continuing to stir for 18 minutes to obtain a gel, vacuum filtering the gel to obtain a filter cake, adding the filter cake to an 8% ethanol aqueous solution, controlling the speed to be stirred at 600 rpm for 16 minutes until uniform, adjusting the pH value to 8.8 with a 0.002% sodium hydroxide aqueous solution, then adding tetraethyl orthosilicate, heating to 50°C, maintaining the speed unchanged, continuing to stir the reaction for 1.2 hours, centrifuging, and washing the precipitate with anhydrous ethanol and deionized water three times each, and drying at 55°C to constant weight to obtain core-shell particles, wherein the mass ratio of saturated aluminum sulfate solution, sodium aluminate aqueous solution, tetraethyl orthosilicate and ethanol aqueous solution is 10:18:50:450;
[0037] Step A2, the core-shell particles were added to deionized water, heated to 35 ° C, and ultrasonically treated for 8 min at an ultrasonic frequency of 30 kHz and an ultrasonic power of 450 w until uniform, the speed was controlled at 460 rpm, and a mixture of γ-aminopropyltriethoxysilane and anhydrous ethanol a was added dropwise while stirring, and the dripping was controlled within 15 min. After the dripping was completed, the temperature was raised to 45 ° C, the speed was maintained unchanged, and the stirring reaction was continued for 2.2 h. Centrifugation was performed, and the precipitate was washed 3 times with anhydrous ethanol and deionized water respectively, and dried to constant weight at 58 ° C to obtain an enhanced component, wherein the mass ratio of core-shell particles, deionized water and mixed solution a was 3:55:28, and the mass ratio of γ-aminopropyltriethoxysilane and anhydrous ethanol in the mixed solution a was 0.4:30.
[0038] Preparation Example 2
[0039] This preparation example provides a reinforcing component, which is prepared by the following steps:
[0040] Step A1, at a speed of 560 rpm, adding a saturated aluminum sulfate solution dropwise to a sodium aluminate aqueous solution while stirring, controlling the dripping to be completed within 15 minutes, maintaining the speed unchanged, and continuing to stir for 20 minutes to obtain a gel, vacuum filtering the gel to obtain a filter cake, adding the filter cake to a 10% ethanol aqueous solution, controlling the speed to be stirred at 630 rpm for 18 minutes until uniform, adjusting the pH value to 9.0 with a 0.004% sodium hydroxide aqueous solution, then adding tetraethyl orthosilicate, heating to 58°C, continuing to stir the reaction for 1.4 hours, centrifuging, and washing the precipitate with anhydrous ethanol and deionized water 4 times each, and drying at 60°C to constant weight to obtain core-shell particles, wherein the mass ratio of saturated aluminum sulfate solution, sodium aluminate aqueous solution, tetraethyl orthosilicate and ethanol aqueous solution is 12:24:55:500;
[0041] Step A2, the core-shell particles were added to deionized water, heated to 40 ° C, and ultrasonically treated for 10 min at an ultrasonic frequency of 35 kHz and an ultrasonic power of 500 w until uniform, the speed was controlled at 500 rpm, and a mixture of γ-aminopropylmethyldiethoxysilane and anhydrous ethanol was added dropwise while stirring. The mixture was controlled to drip within 15 minutes. After the dripping was completed, the temperature was raised to 50 ° C, the speed was maintained unchanged, and the stirring reaction was continued for 2.3 hours. Centrifugation was performed, and the precipitate was washed 4 times with anhydrous ethanol and deionized water respectively, and dried at 62 ° C to constant weight to obtain an enhanced component, wherein the mass ratio of core-shell particles, deionized water and mixed solution a was 4:60:30, and the mass ratio of γ-aminopropylmethyldiethoxysilane and anhydrous ethanol in the mixed solution a was 0.8:30.
[0042] Preparation Example 3
[0043] This preparation example provides a reinforcing component, which is prepared by the following steps:
[0044] Step A1, at a speed of 580 rpm, while stirring, a saturated aluminum sulfate solution was added dropwise to a sodium aluminate aqueous solution, and the dripping was controlled to be completed within 15 minutes. After the dripping was completed, the speed was maintained unchanged and stirring was continued for 22 minutes to obtain a gel, and the gel was vacuum filtered to obtain a filter cake. The filter cake was added to a 12% ethanol aqueous solution by mass, and the speed was controlled to be 660 rpm and stirred for 20 minutes until uniform. The pH value was adjusted to 9.2 with a 0.006% sodium hydroxide aqueous solution, and then ethyl orthosilicate was added. The temperature was raised to 66° C. and the reaction was continued with stirring for 1.6 hours. The precipitate was washed with anhydrous ethanol and deionized water 5 times each, and dried at 65° C. to constant weight to obtain core-shell particles, wherein the mass ratio of saturated aluminum sulfate solution, sodium aluminate aqueous solution, ethyl orthosilicate and ethanol aqueous solution was 14:30:60:550;
[0045] Step A2, the core-shell particles were added to deionized water, heated to 45 ° C, and ultrasonically treated for 12 min at an ultrasonic frequency of 40 kHz and an ultrasonic power of 550 w until uniform, the speed was controlled to 540 rpm, and a mixture of γ-aminopropyltriethoxysilane and anhydrous ethanol a was added dropwise while stirring, and the dripping was controlled within 15 minutes. After the dripping was completed, the temperature was raised to 55 ° C, the speed was maintained unchanged, and the stirring reaction was continued for 2.4 hours. Centrifugation was performed, and the precipitate was washed 5 times with anhydrous ethanol and deionized water respectively, and dried at 66 ° C to constant weight to obtain an enhanced component, wherein the mass ratio of core-shell particles, deionized water and mixed solution a was 5:65:32, and the mass ratio of γ-aminopropyltriethoxysilane and anhydrous ethanol in the mixed solution a was 0.8:30.
[0046] Comparative Preparation Example 1
[0047] This comparative preparation example provides a reinforcing component, which is prepared by the following steps:
[0048] Step A1, at a speed of 540 rpm, while stirring, a saturated aluminum sulfate solution was added dropwise to a sodium aluminate aqueous solution, and the dripping was controlled to be completed within 15 minutes. After the dripping was completed, the speed was maintained unchanged and the stirring was continued for 18 minutes to obtain a gel. The gel was vacuum filtered to obtain a filter cake, and the filter cake was added to an 8% ethanol aqueous solution, and the speed was controlled to be 600 rpm and stirred for 16 minutes until uniform. The pH value was adjusted to 8.8 with a 0.002% sodium hydroxide aqueous solution, and tetrabutyl titanate was added. The temperature was raised to 50°C, the speed was maintained unchanged, and the reaction was continued with stirring for 1.2 hours. The precipitate was washed with anhydrous ethanol and deionized water three times each, and dried at 55°C to constant weight to obtain core-shell particles, wherein the mass ratio of the saturated aluminum sulfate solution, the sodium aluminate aqueous solution, the tetrabutyl titanate and the ethanol aqueous solution was 10:18:50:450;
[0049] Step A2, the core-shell particles were added to deionized water, heated to 35 ° C, and ultrasonically treated for 8 min at an ultrasonic frequency of 30 kHz and an ultrasonic power of 450 w until uniform, the speed was controlled at 460 rpm, and a mixture of γ-aminopropyltriethoxysilane and anhydrous ethanol a was added dropwise while stirring, and the dripping was controlled within 15 min. After the dripping was completed, the temperature was raised to 45 ° C, the speed was maintained unchanged, and the stirring reaction was continued for 2.2 h. Centrifugation was performed, and the precipitate was washed 3 times with anhydrous ethanol and deionized water respectively, and dried to constant weight at 58 ° C to obtain an enhanced component, wherein the mass ratio of core-shell particles, deionized water and mixed solution a was 3:55:28, and the mass ratio of γ-aminopropyltriethoxysilane and anhydrous ethanol in the mixed solution a was 0.4:30.
[0050] Comparative Preparation Example 2
[0051] This comparative preparation example provides a reinforcing component, which is prepared by the following steps:
[0052] This preparation example provides a reinforcing component, which is prepared by the following steps:
[0053] Step A1, at a speed of 540 rpm, adding a saturated aluminum sulfate solution dropwise to a sodium aluminate aqueous solution while stirring, controlling the dripping to be completed within 15 minutes, maintaining the speed unchanged, and continuing to stir for 18 minutes to obtain a gel, vacuum filtering the gel to obtain a filter cake, adding the filter cake to an 8% ethanol aqueous solution, controlling the speed to be stirred at 600 rpm for 16 minutes until uniform, adjusting the pH value to 8.8 with a 0.002% sodium hydroxide aqueous solution, then adding tetraethyl orthosilicate, heating to 50°C, maintaining the speed unchanged, continuing to stir the reaction for 1.2 hours, centrifuging, and washing the precipitate with anhydrous ethanol and deionized water three times each, and drying at 55°C to constant weight to obtain core-shell particles, wherein the mass ratio of saturated aluminum sulfate solution, sodium aluminate aqueous solution, tetraethyl orthosilicate and ethanol aqueous solution is 10:18:50:450;
[0054] Step A2, the core-shell particles were added to deionized water, heated to 35 ° C, and ultrasonically treated for 8 min at an ultrasonic frequency of 30 kHz and an ultrasonic power of 450 w until uniform, the speed was controlled at 460 rpm, and a mixture of γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol a was added dropwise while stirring, and the dripping was controlled within 15 minutes. After the dripping was completed, the temperature was raised to 45 ° C, the speed was maintained unchanged, and the stirring reaction was continued for 2.2 hours. Centrifugation, the precipitate was washed, and dried at 58 ° C to constant weight to obtain an enhanced component, wherein the mass ratio of core-shell particles, deionized water and mixed solution a was 3:55:28, and the mass ratio of γ-glycidyloxypropyltrimethoxysilane and anhydrous ethanol in the mixed solution a was 0.4:30.
[0055] Preparation Examples 4-6 and Comparative Preparation Examples 3-4 provide a functionalized adhesive.
[0056] Preparation Example 4
[0057] This preparation example provides a functionalized adhesive, which is prepared by the following steps:
[0058] Dopamine and polyacrylic acid were added to a Tris-HCl buffer solution with a pH of 8, stirred at 600 rpm for 5 minutes until uniform, and then 30% by mass of silica sol was added. The rotation speed was adjusted to 1000 rpm, the temperature was raised to 34°C, and stirring was continued for 12 minutes to obtain a functionalized binder, wherein the mass ratio of dopamine, polyacrylic acid, Tris-HCl buffer solution and silica sol was 2:10:50:0.8.
[0059] Preparation Example 5
[0060] This preparation example provides a functionalized adhesive, which is prepared by the following steps:
[0061] Dopamine and polyacrylic acid were added to a Tris-HCl buffer solution with a pH of 8.5, stirred at 620 rpm for 7 minutes until uniform, and then a silica sol with a mass fraction of 35% was added, the speed was adjusted to 1100 rpm, and stirring was continued for 14 minutes to obtain a functionalized binder, wherein the mass ratio of dopamine, polyacrylic acid, Tris-HCl buffer solution and silica sol was 2.5:12:55:1.0.
[0062] Preparation Example 6
[0063] This preparation example provides a functionalized adhesive, which is prepared by the following steps:
[0064] Dopamine and polyacrylic acid were added to a Tris-HCl buffer solution with a pH of 9, and stirred at a speed of 640 rpm for 9 minutes until uniform. Then, silica sol with a mass fraction of 40% was added, the speed was adjusted to 1200 rpm, the temperature was raised to 37°C, and stirring was continued for 16 minutes to obtain a functionalized binder, wherein the mass ratio of dopamine, polyacrylic acid, Tris-HCl buffer solution and silica sol was 3:14:60:1.2.
[0065] Comparative Preparation Example 3
[0066] This comparative preparation example provides a functionalized adhesive, which is prepared by the following steps:
[0067] Polyacrylic acid was added to a Tris-HCl buffer solution with a pH of 8, and the mixture was stirred at a speed of 600 rpm for 5 minutes until uniform. Then, 20% by mass of silica sol was added, the rotation speed was adjusted to 1000 rpm, the temperature was raised to 40°C, and stirring was continued for 12 minutes to obtain a functionalized binder, wherein the mass ratio of polyacrylic acid, Tris-HCl buffer solution and silica sol was 10:50:0.8.
[0068] Comparative Preparation Example 4
[0069] This comparative preparation example provides a functionalized adhesive, which is prepared by the following steps:
[0070] Dopamine and polyvinyl alcohol were added to a Tris-HCl buffer solution with a pH of 8, stirred at a speed of 600 rpm for 5 minutes until uniform, and then a silica sol with a mass fraction of 20% was added. The speed was adjusted to 1000 rpm, the temperature was raised to 34°C, and stirring was continued for 12 minutes to obtain a functionalized adhesive, wherein the mass ratio of dopamine, polyvinyl alcohol, Tris-HCl buffer solution and silica sol was 2:10:50:0.8.
[0071] Examples 1-3 and Comparative Examples 1-4 provide a method for preparing a photochromic functional ceramic material.
[0072] Example 1
[0073] This embodiment provides a method for preparing a photochromic functional ceramic material, comprising the following steps:
[0074] Step S1, primary grinding: niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide, and anhydrous ethanol were mixed, the ball mill speed was controlled to 480 rpm, the ball milling time was 26 hours, the mixture was dried at 60° C., and passed through a 300-mesh sieve to obtain a primary grinding material, wherein the mass ratio of niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide, and anhydrous ethanol was 36.3:1:7.3:0.17:500;
[0075] Step S2, preparing a photochromic material: placing the primary ground material in a high-temperature sintering furnace, heating it to 920° C. at a heating rate of 1° C. / min, and cooling it to room temperature to obtain a photochromic material;
[0076] Step S3, preparing a green body: adding a photochromic material to an ethanol aqueous solution with a mass fraction of 8%, performing secondary grinding, controlling the secondary grinding time to 14 minutes, then adding the reinforcing component prepared in Preparation Example 1, the functionalized binder prepared in Preparation Example 4, and p-toluenesulfonic acid, stirring at a speed of 900 rpm for 12 minutes until uniform, then placing in a mold, performing dry pressing, controlling the pressure to 6 MPa, holding the pressure for 1 minute, and then performing cold isostatic pressing at a pressure of 260 MPa, a cold isostatic pressing temperature of 64°C, and a cold isostatic pressing time of 2 minutes to obtain a green body, wherein the mass ratio of the photochromic material, the ethanol aqueous solution, the reinforcing component, the functionalized binder, and the p-toluenesulfonic acid is 90:42:8:10:0.2;
[0077] Step S4, preparing a photochromic functional ceramic material: placing the green body into an alumina crucible, placing it in a high-temperature box furnace, heating it to 540°C at a heating rate of 1°C, keeping it warm for 4.5 hours, then heating it to 1220°C at a heating rate of 3°C / min, keeping it warm for 3.6 hours, and cooling it to room temperature to obtain a photochromic functional ceramic material.
[0078] Example 2
[0079] This embodiment provides a method for preparing a photochromic functional ceramic material, comprising the following steps:
[0080] Step S1, primary grinding: niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide, and anhydrous ethanol were mixed, the ball mill speed was controlled to 510 rpm, the ball milling time was 24 hours, the mixture was dried at 64° C., and the mixture was passed through a 320-mesh sieve to obtain a primary grinding material, wherein the mass ratio of niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide, and anhydrous ethanol was 36.3:3:10.2:0.19:550;
[0081] Step S2, preparing a photochromic material: placing the primary ground material in a high-temperature sintering furnace, heating it to 950° C. at a heating rate of 2° C. / min, keeping the temperature for 2.0 h, and cooling it to room temperature to obtain a photochromic material;
[0082] Step S3, preparing a green body: adding a photochromic material to a 10% mass fraction of an ethanol aqueous solution, performing secondary grinding, controlling the secondary grinding time to 18 minutes, then adding the reinforcing component prepared in Preparation Example 2 and the functionalized binder prepared in Preparation Example 5, stirring at a speed of 940 rpm for 14 minutes until uniform, then placing in a mold, performing dry pressing, controlling the pressure to 7 MPa, holding the pressure for 1.5 minutes, and then performing cold isostatic pressing at a pressure of 290 MPa, a cold isostatic pressing temperature of 68°C, and a cold isostatic pressing time of 3 minutes to obtain a green body, wherein the mass ratio of the photochromic material, the ethanol aqueous solution, the reinforcing component, the functionalized binder, and the pyridine is 95:44:10:13:0.4;
[0083] Step S4, preparing a photochromic functional ceramic material: placing the green body into an alumina crucible, placing it in a high-temperature box furnace, heating it to 550°C at a heating rate of 2°C, keeping it warm for 5 hours, then heating it to 1240°C at a heating rate of 4°C / min, keeping it warm for 3.8 hours, and cooling it to room temperature to obtain a photochromic functional ceramic material.
[0084] Example 3
[0085] This embodiment provides a method for preparing a photochromic functional ceramic material, comprising the following steps:
[0086] Step S1, primary grinding: niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide, and anhydrous ethanol were mixed, the ball mill speed was controlled to 540 rpm, the ball milling time was 22 hours, the mixture was dried at 68° C., and the mixture was passed through a 340-mesh sieve to obtain a primary grinding material, wherein the mass ratio of niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide, and anhydrous ethanol was 36.3:3:10.2:0.19:550;
[0087] Step S2, preparing a photochromic material: placing the primary ground material in a high-temperature sintering furnace, heating it to 980° C. at a heating rate of 3° C. / min, and cooling it to room temperature to obtain a photochromic material;
[0088] Step S3, preparing a green body: adding a photochromic material to an ethanol aqueous solution with a mass fraction of 12%, performing secondary grinding, controlling the secondary grinding time to 22 minutes, then adding the reinforcing component prepared in Preparation Example 3, the functionalized binder prepared in Preparation Example 6, and p-toluenesulfonic acid, stirring at a speed of 980 rpm for 16 minutes until uniform, then placing in a mold, performing dry pressing, controlling the pressure to 8 MPa, holding the pressure for 2 minutes, and then performing cold isostatic pressing at a pressure of 320 MPa, a cold isostatic pressing temperature of 72° C., and a cold isostatic pressing time of 4 minutes to obtain a green body, wherein the mass ratio of the photochromic material, the ethanol aqueous solution, the reinforcing component, the functionalized binder, and the p-toluenesulfonic acid is 100:46:12:16:0.6;
[0089] Step S4, preparing a photochromic functional ceramic material: placing the green body into an alumina crucible, placing it in a high-temperature box furnace, heating it to 560°C at a heating rate of 3°C, keeping it warm for 5.5 hours, then heating it to 1320°C at a heating rate of 5°C / min, keeping it warm for 4 hours, and cooling it to room temperature to obtain a photochromic functional ceramic material.
[0090] Comparative Example 1
[0091] Comparative Example 1 is the same as Example 1, except that the reinforcing component in Example 1 is replaced by the reinforcing component prepared in Comparative Preparation Example 1.
[0092] Comparative Example 2
[0093] Comparative Example 2 is the same as Example 1, except that the reinforcing component in Example 1 is replaced by the reinforcing component prepared in Comparative Preparation Example 2.
[0094] Comparative Example 3
[0095] Comparative Example 3 is the same as Example 1, except that the functionalized adhesive in Example 1 is replaced by the functionalized adhesive prepared in Comparative Preparation Example 3.
[0096] Comparative Example 4
[0097] Comparative Example 4 is the same as Example 1, except that the functionalized adhesive in Example 1 is replaced by the functionalized adhesive prepared in Comparative Preparation Example 4.
[0098] Performance testing
[0099] The performance of the photochromic functional ceramic materials prepared in Examples 1-3 and Comparative Examples 1-4 was tested.
[0100] Vickers hardness test: GB / T 16534-2009 "Test method for room temperature hardness of fine ceramics" was used to test the Vickers hardness of the photochromic functional ceramic material prepared above.
[0101] Bending strength test: The bending strength of the photochromic functional ceramic material prepared above was tested according to GB / T6569-2006 "Test method for bending strength of fine ceramics";
[0102] Fracture toughness test: The fracture toughness value of the photochromic functional ceramic material prepared above was tested according to GB / T 23806-2009 "Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method";
[0103] Table 1 Performance parameters of photochromic functional ceramic materials prepared in Examples 1-3 and Comparative Examples 1-4
[0104] Test performance Vickers hardness / GPa Bending strength / MPa <![CDATA[Fracture toughness / MPa•m 1 / 2 > Example 1 5.52 268 2.6 Example 2 5.61 274 2.9 Example 3 5.57 265 2.4 Comparative Example 1 4.86 245 1.9 Comparative Example 2 5.26 236 2.1 Comparative Example 3 4.63 181 1.6 Comparative Example 4 4.74 206 1.7
[0105] It can be seen from Table 1 that, compared with Comparative Examples 1-4, the photochromic functional ceramic materials prepared in Examples 1-3 have better mechanical strength.
[0106] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed, but as long as they are within the scope of the claims of the present invention, they are protected by patent law.
Claims
1. A photochromic functional ceramic material, characterized in that: including reinforcing components, photochromic materials, functionalized binders, catalysts and solvents; The reinforcing component is first prepared by precipitation of saturated aluminum sulfate solution and sodium metaaluminate aqueous solution to obtain gel, then coated with nano-silica obtained by hydrolysis of ethyl orthosilicate to obtain core-shell particles, and then modified with a silane coupling agent; The photochromic material is prepared by calcining niobium pentoxide, lithium carbonate, sodium carbonate and praseodymium oxide; The functionalized adhesive is prepared by compounding dopamine, polyacrylic acid and silica sol.
2. The photochromic functional ceramic material according to claim 1, characterized in that: The reinforcing component is prepared by the following steps: Step A1, adding a saturated aluminum sulfate solution dropwise to a sodium metaaluminate aqueous solution while stirring, controlling the complete addition within 15 minutes, and continuing stirring for 18-22 minutes to obtain a gel, vacuum filtering the gel to obtain a filter cake, adding the filter cake to an ethanol aqueous solution, stirring evenly, adjusting the pH to 8.8-9.2, adding ethyl orthosilicate, heating to 50-66° C., continuing stirring to react for 1.2-1.6 hours, centrifuging, washing the precipitate, and drying to obtain core-shell particles; Step A2: Add the core-shell particles to deionized water, heat to 35-45°C, and ultrasonicate for 8-12 minutes. Add the mixture of silane coupling agent and anhydrous ethanol dropwise while stirring. The mixture should be added within 15 minutes. After the addition is complete, heat to 45-55°C and stir for 2.2-2.4 hours. After centrifugation, the precipitate is washed and dried to obtain the enhanced component.
3. The photochromic functional ceramic material according to claim 2, characterized in that: In the step A1, the mass ratio of the saturated aluminum sulfate solution, the sodium metaaluminate aqueous solution, the ethyl orthosilicate and the ethanol aqueous solution is 10-14:18-30:50-60:450-550.
4. The photochromic functional ceramic material according to claim 2, characterized in that: In step A2, the mass ratio of the core-shell particles, deionized water, and the mixed solution a is 3-5:55-65:28-32, and in the mixed solution a, the mass ratio of the silane coupling agent to anhydrous ethanol is 0.4-0.8:
30.
5. The photochromic functional ceramic material according to claim 1, characterized in that: The functionalized binder is prepared by the following steps: Dopamine and polyacrylic acid are added to a Tris-HCl buffer solution with a pH of 8-9, stirred evenly, and then silica sol is added. The temperature is raised to 34-40° C., and stirring is continued for 12-16 minutes to obtain a functionalized adhesive.
6. The photochromic functional ceramic material according to claim 5, characterized in that: The mass ratio of the dopamine, polyacrylic acid, Tris-HCl buffer and silica sol is 2-3:10-14:50-60:0.8-1.
2.
7. The photochromic functional ceramic material according to claim 1, characterized in that: In step S1, the mass ratio of niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide and anhydrous ethanol is 36.3:1-5:7.3-13.1:0.17-0.21:500-600, and the wet ball milling treatment is specifically as follows: the ball milling speed is 480-540 rpm, and the ball milling time is 22-26 hours.
8. The photochromic functional ceramic material according to claim 1, characterized in that: In step S3, the mass ratio of the photochromic material, the solvent, the reinforcing component, the functionalized binder and the catalyst is 90-100:42-46:8-12:10-16:0.2-0.
6.
9. The photochromic functional ceramic material according to any one of claims 1 to 8, characterized in that: Specifically prepared by the following steps: Step S1, primary grinding: mixing niobium pentoxide, lithium carbonate, sodium carbonate, praseodymium oxide and anhydrous ethanol, wet ball milling, drying, and sieving to obtain a primary grinding material; Step S2, preparing a photochromic material: placing the primary ground material in a high-temperature sintering furnace for pre-sintering, and cooling to room temperature to obtain a photochromic material; Step S3, preparing a green body: adding the photochromic material to a solvent, performing secondary grinding, then adding a reinforcing component and a functionalized binder, stirring evenly, placing the green body in a mold, and performing dry pressing and cold isostatic pressing to obtain a green body; Step S4, preparing a photochromic functional ceramic material: placing the green body into an alumina crucible, placing it in a high-temperature box furnace, performing a binder removal process, then performing high-temperature sintering, and cooling to room temperature to obtain a photochromic functional ceramic material.
10. Use of the photochromic functional ceramic material according to claim 9 in functional ceramic parts.
Citation Information
Patent Citations
Photochromic ceramic tile and preparation method thereof
CN106396405A
High-hardness alumina-based ceramic and preparation method thereof
CN118344128A
Thermal insulation composite board core material, preparation method thereof and thermal insulation composite board
CN118812215A
Coating material composition, coating film and optical article with coating film
JP2015151489A
Method for manufacturing ceramic material, ceramic material and use of ceramic material
US20250214900A1